EVALUASI PENGUNAAN (USABILITY) WEBSITE E-PEMERINTAHAN DI KANTOR KELURAHAN DEMANG LEBAR DAUN KOTA PALEMBANG - Sri wahyuni; Doris Febriyanti; Novia Kencana (UIR PRESS, 2023)
F-government implementation is an effort to develop electronic-based governance to improve the quality of public services more effectively and efficiently. The city of Palembang is one of the cities in Indonesia that is trying to develop E-government in carrying out administrative affairs in its government. However, in the continuation of the use of E-government in the city of Palembang, many face problems and various problems so that it has not been able to run optimally as expected. to the people of Palembang. The purpose of this research is to find out how to evaluate the use of e-government websites at the Demang Lebaran urban village office. The theory used in this study uses a model developed by Stuflebeam known as the CIPP Evaluation Model. CIPP stands for this theory indicator, namely Context, Input, Process, Product. The results of this study indicate that the use of e-government websites among the people of the village of Demang Lebar Daun has not been going well until now. This is because there is still little public interest in using the website, this is because people think it is easier to do offline services to the office. Another obstacle reason is that there are still many people who are not digitally literate and are not accustomed to using cellphone devices, especially among the elderly. . So that this is a big task for the village of Demang Lebar Daun to continue to try to maximize the function of this e-government website.